ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI EKSPOR UDANG BEKU INDONESIA KE AMERIKA SERIKAT - Ramanti, Ida Ayu Intan; Budiningsih, Ni Ketut; Ayuningsasi, Anak Agung Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.11.TAHUN.2024DO - 10.24843/EEB.2024.v13.i11.p08, 2024)
Indonesia is a maritime country with abundant natural resources.  There are various types of marine and fishery products that Indonesia has exported. The leading commodities in the fisheries sector is shrimp, where 88.5% of Indonesian shrimp are exported in frozen form. Throughout 2015-2021, the volume of Indonesian frozen shrimp exports to the United States fluctuated. Several factors cause the fluctuation in the volume of frozen shrimp exports. This study aims to determine the effect of United States GDP, export prices, and United States Dollar exchange rates simultaneously and partially on the volume of frozen shrimp exports in Indonesia. This study uses time series data from 2015-2021 in monthly form. The analysis technique used in this study is using multiple linear regression analysis. The results of this study indicate that United States GDP, export prices, and United States Dollar exchange rates have a simultaneous and significant effect on the volume of frozen shrimp exports from Indonesia to the United States. Partially, United States GDP and export prices do not affect while the United States Dollar exchange rate has a positive and significant effect on the volume of frozen shrimp exports from Indonesia to the United States.